Análise dos choques de preço e comportamentos anticompetitivos na precificação da gasolina nos postos de Fortaleza - Nunes, Paulo Henrique de Castro (2021)
The fuel sector is an activity of wide and notable relevance, which represents a significant portion of the household budget. On the other hand, the sector is constantly the target of complaints about anticompetitive practices such as price cartelization. Thus, this paper analyzes whether changes in Petrobras´ prices and the ICMS reference price contribute to an eventual collusion in resale of common gasoline at the gas stations in the city of Fortaleza. In order to view the so-called collusion, the ratio between the average price and standard deviation as for posts based on Fortaleza was employed. Further, two equations were estimated by means of ordinary least squares as to shed light the effect from prices entertained by Petrobras as well as ICMS reference price on the average price and standard deviation. The results showed that both the market structure concentrated in Petrobras is included, as the taxation criterion adopted by the state of Ceará, seem to favor a standardization of pricing strategies.